JUDICIAL REFORMS IN THE CONDITIONS OF NEW UZBEKISTAN IMPROVEMENT ISSUES (World Bulletin of Management and Law, 2023)
In a democratic state, the judicial power acts between the state and the citizen and serves to more effectively ensure the rights and interests of not only the individual, but also the state. It can be clearly said that the judicial power must protect the rights of citizens from any illegal actions and decisions, regardless of who they are made by, including from officials who have the power of authority, and thereby ensure the rule of law. As a body of judicial power, all types of courts are specially established state bodies - subjects of law enforcement activity. This article discusses the reforms in the judicial system in the Republic of Uzbekistan.
Keywords: Judicial Power; Republic of Uzbekistan